The cathedral and the bazaar : musings on Linux and open source by an accidental revolutionary - Raymond, Eric S. (O'Reilly, 2001)
"It all started with a series of odd statistics. The leading challenger to Microsoft's stranglehold on the computer industry is an operating system called Linux, the product of thousands of volunteer programmers who collaborate over the Internet. The software behind a majority of all the world's web sites doesn't come from a big company either, but from a loosely coordinated group of volunteer programmers called the Apache Group. The Internet itself, and much of its core software, was developed through a process of networked collaboration." "This book starts out with A Brief History of Hackerdom - the historical roots of the open-source movement - and details the events that led to the recognition of the power of open source. It contains the full text of The Cathedral and the Bazaar, updated and expanded for this book, plus Mr. Raymond's other key essays on the social and economic dynamics of open-source software development." "Open source is the competitive advantage in the Internet Age. The Cathedral and the Bazaar is a must read for anyone who cares about the computer industry or the dynamics of the information economy. Already, billions of dollars have been made and lost based on the ideas in this book. Its conclusions will be studied, debated, and implemented for years to come."--Jacket